Peningkatan Keterampilan Menulis Paragraf Melalui Menulis Jurnal dan Pemanfaatannya Untuk Penilaian Autentik - Dianel Rofika (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this study is to get a study of the effort to improve the skills of writing paragraphs of students of class VIII SMP Negeri 2 Gebang district Langkat through the activities of journal writing and utilization for authentic assessment. The subjects of this study were students of grade VIII-B SMP Negeri 2 Gebang Langkat district. The results of this study demonstrate that by the practice of continuous journal writing, students become accustomed to writing paragraphs and their paragraph writing skills increase. Indicators of increasing the ability to write the paragraph can be seen from three things: (1) the quantity of ideas generated, (2) the quality of the paragraph: and i: the study activity and motivation. Keywords: writing, paragraph, journal, authentic Abstrak: Tujuan penelitian ini adalah mendapatkan kajian tentang upaya meningkatkan keterampilan menulis paragraf siswa kelas VIII SMP Negeri 2 Gebang kabupaten Langkat melalui kegiatan menulis jurnal dan pemanfaatannya untuk penilaian autentik. Subjek penelitian ini adalah siswa kelas VIII-B SMP Negeri 2 Gebang kabupaten Langkat. Hasil penelitaan tindakan ini menunjukkan bahwa dengan pem-biasaan menulis jurnal secara berkelanjutan, siswa menjadi terbiasa menulis paragraf dan keterampilan menulis paragrafnya pun meningkat. Indikator peningkatan keterampiian menulis paragraf tersebut dapat dilihat dari tiga hal yaitu (1) kuantitas gagasan yang dihasilkan, (2) kualitas paragraf: dan i:cantus asan aktivitas dan motivasi siswa. Kata kunci: menulis, paragraph, jurnal, autentik